2012
DOI: 10.1159/000343803
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and the Cardiorenal Metabolic Syndrome: Therapeutic Modalities and Their Efficacy in Improving Cardiovascular and Renal Risk Factors

Abstract: The prevalence of obesity has increased rapidly in the United States. Obesity affects about one third of the adult population and, even though it is attributed to excess calorie intake and inadequate physical activity, its etiopathogenesis is much more complex and is an area of active study. Lifestyle modifications (with a focus on increased activity and decreased calorie intake) have modest efficacy in the treatment of obesity. There is a dearth of safe and effective therapeutic modalities to treat obesity. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 127 publications
0
19
0
Order By: Relevance
“…For example, there is evidence for a hypothalamus selective resistance to the metabolic actions leptin while its sympathetic nervous system activation effects on organs such as the kidneys are maintained [59]. The proinflammatory adipocytokine tumor necrosis factor α has been shown to promote macrophage recruitment and infiltration with consequent glomerular and tubulointerstitial inflammation as well as to promote upregulation of other inflammatory cytokines which promote kidney tissue fibrosis [64,65,66,67,68]. On the other end of the spectrum in obesity, there is a reduction in the anti-inflammatory adiponectin, and this reduction is associated with increases in albuminuria as well as kidney tissue fibrosis [62,65].…”
Section: Impact Of Obesity On the Kidney Distinct From That Of The Prmentioning
confidence: 99%
“…For example, there is evidence for a hypothalamus selective resistance to the metabolic actions leptin while its sympathetic nervous system activation effects on organs such as the kidneys are maintained [59]. The proinflammatory adipocytokine tumor necrosis factor α has been shown to promote macrophage recruitment and infiltration with consequent glomerular and tubulointerstitial inflammation as well as to promote upregulation of other inflammatory cytokines which promote kidney tissue fibrosis [64,65,66,67,68]. On the other end of the spectrum in obesity, there is a reduction in the anti-inflammatory adiponectin, and this reduction is associated with increases in albuminuria as well as kidney tissue fibrosis [62,65].…”
Section: Impact Of Obesity On the Kidney Distinct From That Of The Prmentioning
confidence: 99%
“…Conversely, a reduction in plasmin activation is also associated with reduced activation of transforming growth factor-␤ (TGF-␤), a molecule important for suppressing the proliferation and migration of smooth muscle cells that contributes to atherosclerotic lesion formation (71). This highlights the association of excess nutrient ingestion and obesity in driving CVD and CKD with various components of the CRS (29,70).…”
Section: Overnutrition Obesity and Cardiovascular Diseasesmentioning
confidence: 99%
“…Many persons with the metabolic syndrome will also have evidence of insipid renal and cardiovascular disease, and, thus, the CRS constellation. Overweight or obesity, especially abdominal obesity, caused by consumption of excess nutrients, especially high fructose and fat, has been increasingly implicated as an independent risk factor for development of diabetes, cardiovascular disease (CVD), and chronic kidney disease (CKD) (29). Indeed, obesity is a proinflammatory, prooxidative, and maladaptive immune state associated with the accumulation of dysfunctional adipose tissue, altered vascular homeostasis, and endothelial dysfunction, which predisposes individuals to CVD and CKD (30).…”
mentioning
confidence: 99%
“…Overweight or obesity, especially abdominal obesity, has become an independent risk factor for many diseases such as cardiovascular diseases, diabetes, multiple types of cancer and renal diseases [33,34]. It has been reported that mice consuming a Western diet manifested increased heart and vascular fibrosis which further resulted in cardiac hypertrophy and dysfunction [35].…”
Section: Discussionmentioning
confidence: 99%